Defence management : an introduction - Bucur-Marcu, Hari.; Fluri, Philipp, 1960-; Tagarev, Todor (Geneva : Geneva Centre for the Democratic Control of Armed Forces, 2009)
His first volume in the Security and Defence Management Series focuses on practical aspects of democratic defence management through the eyes of practioners. Outlining in simple terms the key issues defence professionals must address to ensure good governance of the defence sector from within the defence establishment, the book provides an introduction to these issues for new defence professionals in transition democracies.
Preface -- Philipp Fluri -- Introduction -- Hari Bucur-Marcu -- Governance, Management, Command, Leadership: Setting the Context for Studies of Defence Management -- Valeri Ratchev -- Defence Planning-Core Processes in Defence Management -- Todor Tagarev -- Introduction to Program-based Force Development -- Todor Tagarev -- Managing Finances -- Gerd Frorath -- Manpower Management -- Jack Treddenick -- Acquisition Management -- Anthony Lawrence -- Transparency in Defence Management -- William F. van Eekelen.
Keywords: Armed Forces -- Management; Military administration; Military administration -- Defenses